Pengaruh Indeks Keislaman, Pertumbuhan Ekonomi, dan IPM terhadap Kebahagiaan Masyarakat di Wilayah Pesisir Selat Malaka: Studi tentang Indonesia, Malaysia, Singapura, dan Thailand - Muhammad Rizal Akbar (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2024)
Community happiness is an important indicator of the country's welfare and is related to the quality of life. The Malacca Strait Coastal Area, which includes Indonesia, Malaysia, Singapore, and Thailand, has cultural, religious, and economic policy differences that affect people's happiness. This study aims to analyze the influence of the Islamicity Index, economic growth, and Human Development Index (HDI) on happiness in this region. The research method used is a quantitative-descriptive design, with secondary data from 2020 to 2024 covering the Islamicity Index, HDI, and economic growth. Descriptive analysis shows that the Islamicity Index has a significant negative effect on happiness with a coefficient of -0.257985 (p-value 0.0067), while economic growth has a varied impact. HDI had the most significant positive influence with a coefficient of 7.616624 (p-value 0.0000). These findings show that HDI is the dominant factor in increasing happiness, while the Islamicity Index and economic growth require a more inclusive approach. The results of this study are expected to provide insight for policymakers to prioritize increasing HDI to achieve sustainable happiness in the Malacca Strait Coastal area.